If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 172 = 2x + 4(6x + 4) Reorder the terms: 172 = 2x + 4(4 + 6x) 172 = 2x + (4 * 4 + 6x * 4) 172 = 2x + (16 + 24x) Reorder the terms: 172 = 16 + 2x + 24x Combine like terms: 2x + 24x = 26x 172 = 16 + 26x Solving 172 = 16 + 26x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26x' to each side of the equation. 172 + -26x = 16 + 26x + -26x Combine like terms: 26x + -26x = 0 172 + -26x = 16 + 0 172 + -26x = 16 Add '-172' to each side of the equation. 172 + -172 + -26x = 16 + -172 Combine like terms: 172 + -172 = 0 0 + -26x = 16 + -172 -26x = 16 + -172 Combine like terms: 16 + -172 = -156 -26x = -156 Divide each side by '-26'. x = 6 Simplifying x = 6
| 4v^2-12v^2-5v+15=0 | | .20x+.92*10=.65(x+10) | | .75*.75-6= | | 7a^2+22a+3= | | -k=(k-10) | | 2x-6=6-2x | | 36x=81 | | x+21=-8 | | 16=v(v-6) | | 9x-20+6x-5=180 | | 41=-r+32 | | 2x^2-5x-12= | | 9x(4)=81 | | 9x(4)= | | 8T=-4 | | 7x+9=6x+20 | | 3.33x=30 | | 4.5-1.5y=5.4 | | 14x-7+3y-7x-7x= | | 5(2-b)=-3(b-3) | | 9a-7=29 | | 3b^2+26b+48=0 | | 167+19x+16x=1132 | | 4x-2(x-8)=2(x+1)+5 | | 4n+2=3n | | 5x+8y=6n | | -5n=-30 | | 3x+12=9x+9 | | 3x+3/2(2x-1)=2 | | -5x-12=3x-6x | | -5=-30 | | 3q+12=9q+9 |